2020
DOI: 10.1155/2020/3190136
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Half-Time Photodynamic Therapy on Retinal Sensitivity in Eyes with Chronic Central Serous Chorioretinopathy

Abstract: The purpose of this study was to evaluate the long-term effects of half-time photodynamic therapy (PDT) on the retinal sensitivity in eyes with chronic central serous chorioretinopathy (CSC). Twenty-two eyes of 22 patients with chronic CSC were studied. PDT was applied with full-dose verteporfin and half-time laser duration. The best-corrected visual acuity (BCVA) and retinal sensitivity in the central 2 and 10 degrees were evaluated at the baseline, and at 12 and 24 months after the half-time PDT. The retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…In these patients, treatment options are limited. Continuous laser photocoagulation at the fovea would lead to significant vision loss, and PDT could lead to chorioretinal atrophy and CNV formation with significant vision loss [ 24 , 25 ]. Therefore, trans-foveal SML could be the preferred treatment option in patients with limited SRF under the fovea due to the good safety profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, treatment options are limited. Continuous laser photocoagulation at the fovea would lead to significant vision loss, and PDT could lead to chorioretinal atrophy and CNV formation with significant vision loss [ 24 , 25 ]. Therefore, trans-foveal SML could be the preferred treatment option in patients with limited SRF under the fovea due to the good safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a favorable natural course in acute CSC patients, any intervention needs to have an excellent safety profile [ 22 ]. Eplerenone and spironolactone treatment can cause gynecomastia and hyperkalemia [ 23 ]; PDT adverse effects are choroidal hypoperfusion, choroidal neovascularization (CNV), and RPE atrophy [ 24 ]; and focal laser photocoagulation can cause RPE atrophy and CNV [ 17 , 25 ]. SML has a good safety profile as there have been no ocular adverse effects described when using appropriate laser pulse parameters [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of microperimetry utilization in the evaluation of cCSC treatment efficacy can be found in the PLACE trial and SPECTRA trial, which found a significant improvement of retinal sensitivity after half-dose PDT (van Dijk et al, 2018;van Rijssen et al, 2022). Long-term significant benefit of half-dose PDT measured using microperimetry has also been reported in a cohort study (Iwase et al, 2020). Microperimetry remains underutilized in RCTs of cCSC and was not considered as an outcome for this study due to the lack of meta-analytic potential.…”
Section: Discussionmentioning
confidence: 95%
“…Half-time PDT has been shown to be safe and effective for chronic CSC in several retrospective studies [ 31 , 32 ] Liu et al [ 33 ] compared the result of half-time versus half-dose PDT in chronic CSC and showed that there were no significant differences in terms of VA improvement (−0.15 logMAR units versus −0.25 logMAR units) and proportion of complete SRF resolution (100% versus 91%) at 1 year. Similarly, Peng et al [ 34 ] showed no significant differences between half-time and half-dose PDT in terms of VA gain (−0.17 logMAR units versus −0.11 logMAR units) and proportion of complete SRF resolution (94% versus 94%) at 1 year.…”
Section: Efficacy Of Photodynamic Therapy In Different Pachychoroid Diseasesmentioning
confidence: 99%